Mobilizing agencies for incidence surveys on child maltreatment: successful participation in Switzerland and lessons learned - Andreas Jud; Céline Kosirnik; Tanja Mitrovic; Hakim Ben Salah; Etienne Fux; Jana Koehler; Rahel Portmann; René Knüsel (BMC, 2018)
Abstract Background Many countries around the world lack data on the epidemiology of agency response to child maltreatment. They therefore lack information on how many children in need get help and protection or if children stand equal chances across regions to get services. However, it has proven difficult to commit child protection agencies to participation in incidence studies. Methods The Optimus Study invested in a continuous collaborative effort between research and practice to develop a data collection for the first national study on the incidence of agency responses to all forms of child maltreatment in Switzerland. An innovative approach of utilizing individual agencies' standardized data reduced work burden for participation respectably: any arbitrary excerpt of data on new cases between September 1 and November 30, 2016, could be uploaded to a secured web-based data integration platform. It was then mapped automatically to fit the study's definitions and operationalizations. Results This strategy has led to a largely successful participation rate of 76% of agencies in the nationwide sample. 253 agencies from the social and health sector, public child protection, and the penal sector have provided data. Conclusions Valuing agencies context-specific knowledge and expertise instead of viewing them as mere providers of data is a precondition for representativeness of incidence data on agency responses to child maltreatment. Potential investigators of future similar studies might benefit from the lessons learned of the presented project.